Characterization of exonic variants of uncertain significance in very long‐chain acyl‐CoA dehydrogenase identified through newborn screening. Issue 3 (11th March 2022) - D'Annibale, Olivia M.; Koppes, Erik A.; Sethuraman, Meena; Bloom, Kaitlyn; Mohsen, Al‐Walid; Vockley, Jerry
Abstract: Very long‐chain acyl‐CoA dehydrogenase deficiency (VLCADD) is an autosomal recessive disease resulting from mutations in the ACADVL gene and is among the disorders tested for in newborn screening (NBS). Confirmatory sequencing following suspected VLCADD NBS results often identifies variants of uncertain significance (VUS) in the ACADVL gene, leading to uncertainty of diagnosis and providing effective treatment regimen. Currently, ACADVL has >300 VUSs in the ClinVar database that requiring characterization to determine potential pathogenicity. In this study, CRISPR/Cas9 genome editing was used to knock out ACADVL in HEK293T cells, and targeted deletion was confirmed by droplet digital polymerase chain reaction (PCR). No VLCAD protein was detected and an 84% decrease in enzyme activity using the electron transfer flavoprotein fluorescence reduction assay and C21‐CoA as substrate was observed compared to control. Plasmids containing control or variant ACADVL coding sequence were transfected into the ACADVL null HEK293T. While transfection of control ACADVL restored VLCAD protein and enzyme activity, cells expressing the VLCAD Val283Ala mutant had 18% VLCAD enzyme activity and reduced protein compared to control. VLCAD Ile420Leu, Gly179Arg, and Gln406Pro produced protein comparable to control but 25%, 4%, and 5% VLCAD enzyme activity, respectively. Leu540Pro and Asp570_Ala572dup had reduced VLCAD protein and 10% and 3% VLCAD enzyme activity, respectively. VLCADD fibroblasts containing the same variations had decreased VLCAD protein and activity comparable to the transfection experiments. Generating ACADVL null HEK293T cell line allowed functional studies to determine pathogenicity of ACADVL exonic variants. This approach can be applied to multiple genes for other disorders identified through NBS.